Peranan Pemerintah Daerah Dalam Pengembangan Kawasan Pariwisata Tanjung Pallette di Kabupaten Bone - Irmawati Surya (Departemen Ilmu Pemerintahan Fisip Unhas, 2017)
This study aims to determine how the role of local government in this case the Department of Culture and Tourism in the development of tourism destinations, tourism marketing, tourism and human resources development and the factors that influence the development of tourism area of Tanjung Pallette in Bone regency. Type of research is descriptive that aims to outline a systematic, factual and accurate information on the existing data in the field is focused on the role of the Department of Culture and Tourism in the development of tourism areas Tanjung Pallette. From the research results demonstrate that the role of local governmentin the development of tourism areas Tanjung Pallette has aligned with that contained in the Strategic Plan (RENSTRA) Regional Work Unit of Department Education and Culture, but in the execution there are problems one of which is the delay in the disbursement of funds resulting in physical work was not accomplished in accordance with the stipulated time , Destination Development Tanjung Pallette for 2016 focus on improving infrastructure. Development of tourism marketing Tanjung Pallette been conducted by the Department of Culture and Tourism as well as of the tourist administrator attraction, And to tour Cape Pallette Human Resources Development have formed a group gempita that moves euphoria tourism business sector. Supporting factors in tourism development Tanjung Pallette tourism among the Government policy support, community participation, travel around Tanjung Pallette and easy coordination between the parties involved. The limiting factor in the development of tourism Tanjung Pallette Among the limited funds and disbursements are slow, lack of human resources